Nonlinear optical response of Au nanorods for broadband pulse modulation in bulk visible lasers - Wang, Shuxian (2015)
Due to the lack of suitable optical modulators, directly generated Pr3+- and Dy3+-doped bulk visible lasers are limited in the continuous-wave operation; yet, pulsed visible lasers are only sparingly reported recently. It has been theoretically predicated that Au nanorods could modulate the visible light operation, based on the nonlinear optical response of surface plasmon resonance. Here, we demonstrate the saturable absorption properties of Au nanorods in the visible region and experimentally realized the pulsed visible lasers over the spectral range of orange (605 nm), red (639 nm), and deep red (721 nm) with Au nanorods as the optical modulator. We show that Au nanorods have a broad nonlinear optical response and can serve as a type of broadband, low-cost, and eco-friendly candidate for optical switchers in the visible region. Our work also advocates the promise of plasmonic nanostructures for the development of pulsed lasers and other plasmonic devices.